PENGHAMBATAN EKSTRAK METANOL DAUN DAN BATANG TUMBUHAN MANGROVERhizophoramucronataTERHADAP PERTUMBUHAN BEBERAPA STRAIN BAKTERI Aeromonas hydrophila - Heri Maryanto; Ana Miftahul Janah; Dini Siswani Mulia (Universitas Sebelas Maret, 2018)
Aeromonas hydrophila is one of the pathogenic bacteria that attack freshwater fish. These bacteria are also pathogenic in brackish water fish and sea and other aquatic animals. Treatment of this bacterial attack should be pursued by using natural materials that are more effective and environmentally friendly, one of which is Rhizophora mucronata. This study aims to determine the inhibition of methanol extract of leaves and stems of R. mucronata mangrove plant on the growth of several strains of A. hydrophila bacteria. The experiment was conducted using experimental method with Completely Randomized Design (RAL) 3 factor factorial, ie A factor (type of bacterial strain): A1 (GPl-04), A2 (GL-01), A3 (GL-02), A4 (GJ- 01), A5 (GK-01), and A6 (GB-01); B (plant part): B1 (stem) and B2 (leaf); C (concentration of methanol extract R. mucronata): C1 (0% / control), C2 (10%), C3 (20%), and C4 (30%), with 3 replications. The parameters observed were the results of phytochemical screening test by Thin Layer Chromatography (TLC) and bacterial growth inhibition (clear zone). Data of clear zone were analyzed using Analysis of Variance (Anova) and Duncan Multiple Range Test (DMRT) with 5% test level, while the result of phytochemical screening test with TLC was analyzed descriptively qualitative. The results showed that R. mucronata mangrove plants potentially inhibited the growth of A. hydrophila because it contains flavonoids, alkaloids, terpenoids, and tannins. The type of bacterial strain and concentration of R. mucronata methanol extract had significant effect (P0 <0,05) on the inhibitory zone diameter but the plant part and interaction of the three factors, ie strains of bacteria, plant part, and concentration of R. mucronata methanol extract were not significantly different P> 0.05). Plant parts of both stems and leaves have the same potential as a natural bactericidal material. Bacteria A. hydrophila GL-01 strain was most sensitive, whereas GK-01 strain was most resistant to R. mucronata methanol extract. 10% concentration is an effective and efficient concentration in inhibiting the growth of A.hydrophila bacteria.